2017
DOI: 10.1111/bcpt.12797
|View full text |Cite
|
Sign up to set email alerts
|

A 10‐Year Experience of Therapeutic Drug Monitoring (TDM) of Linezolid in a Hospital‐wide Population of Patients Receiving Conventional Dosing: Is there Enough Evidence for Suggesting TDM in the Majority of Patients?

Abstract: A retrospective study was conducted to assess our 10-year experience of therapeutic drug monitoring (TDM) of linezolid in a large patient population to establish whether conventional dosing may result in adequate drug exposure in the majority of patients. Patients included in this study underwent TDM of linezolid trough concentration (C ) during treatment with conventional doses of 600 mg every 12 hr in the period between January 2007 and June 2016. The desired range of C was set between 2 and 7 mg/L (underexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 32 publications
5
45
2
Order By: Relevance
“…Our study indicated that decreased renal function was an influential factor for linezolid‐induced thrombocytopenia, which was also in line with previously published studies . The increased odds of thrombocytopenia in patients with renal dysfunction were explained by previous studies showing that the increased blood concentration of linezolid‐induced by impaired renal function increases the risk of thrombocytopenia . However, the cut‐off value of CLcr as a risk factor varied among studies as follows: <60 mL/min, <50 mL/min or <30 mL/min .…”
Section: Discussionsupporting
confidence: 89%
“…Our study indicated that decreased renal function was an influential factor for linezolid‐induced thrombocytopenia, which was also in line with previously published studies . The increased odds of thrombocytopenia in patients with renal dysfunction were explained by previous studies showing that the increased blood concentration of linezolid‐induced by impaired renal function increases the risk of thrombocytopenia . However, the cut‐off value of CLcr as a risk factor varied among studies as follows: <60 mL/min, <50 mL/min or <30 mL/min .…”
Section: Discussionsupporting
confidence: 89%
“…Multiple postapproval population PK studies using data obtained from infected patients have consistently found renal function to be one of the most important predictors of linezolid CL (8,23,(32)(33)(34). Furthermore, we have previously demonstrated an association between renal impairment (creatinine clearance, Ͻ40 ml/ min) and a linezolid C min of Ͼ7 mg/liter (adjusted odds ratio [aOR], 3.05; 95% CI, 2.23 to 4.15), which is consistent with the findings by Morata and colleagues at the same eGFR threshold (aOR, 4.27; 95% CI, 1.36 to 13.43) (26,27).…”
Section: Discussionsupporting
confidence: 89%
“…Total daily doses of 300 to 1,800 mg/day were evaluated in increments between 150 and 300 mg in order to reflect pragmatic dose adjustments using the available formulations. Target C min values of Ͼ2 mg/liter for efficacy and Ͼ8 mg/liter for toxicity were used to reflect current practice in centers with TDM (27). A linezolid C min of Ͼ8 mg/liter has been associated with Ն50% odds of thrombocytopenia or decrease in platelet precursor cells in prior analyses (21,(23)(24)(25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, results of studies investigating dose adjustment in obese patients under clinical conditions do not yet exist. The fraction of enterococci resistant to linezolid is currently reported to be 1.6% worldwide [46] and the rate is increasing [47][48][49]. In this context, therapeutic drug monitoring is recommended [50,51].…”
Section: Discussionmentioning
confidence: 99%